Postural stability in people with Chronic Obstructive Pulmonary Disease (COPD): a case control study / Mohd Adnan Abdul Hamid - Abdul Hamid, Mohd Adnan (2017)
Current evidence suggests that individual with Chronic Obstructive Pulmonary Disease (COPD) are reported to fall frequently. Research into the deficits of postural stability of individuals with COPD has focused on postural steadiness (static and dynamic stability). However, there remains a lack of studies focused on postural sway in individuals with COPD. Therefore the purpose of this study was to compare the postural stability (Postural sway, static and dynamic stability) measures between individuals diagnosed with COPD and normal healthy subjects. A total of 30 subjects of individuals with COPD and 30 normal age-matched healthy subjects were assessed for postural stability. Outcome measures such as Single Leg Sand Test (SLST), Functional Reach Test (FRT) and Postural stability index (PSI) using BT4 balance board were measured. Individuals were tested for three different tasks such as open eyes, closed eyes and focusing on a single sport using BT4 balance board. Data were not normally distributed. Significant differences were tested using a non-parametric Wilcoxon rank test. There was no significant difference for the demographic variables such as age and Body Mass Index (BMI) at P > 0.05. A significant decline of postural sway parameters was observed in individuals with COPD group as against healthy age-matched group (P < 0.05). Static and dynamic components were also deteriorated in individuals with COPD subjects. Postural sway and static and dynamic components were compromised in individuals with COPD. Additionally, it yielded those simple measures of outcome measure can also be used to detect changes in the balance constituents. Hence, fall prevention strategies should be incorporated in individuals with COPD. These findings have further necessitated the role of preventive strategies and rehabilitation in managing individuals with COPD.